Mechanical and Electrical Contacting of Electronic Components on Textiles by 3D Printing. (2016) - Grimmelsmann, Nils; Martens, Yasmin; Schäl, Patricia; Meissner, Hubert; Ehrmann, Andrea
Abstract: Materials nowadays become smarter and "more intelligent", containing novel functionalities or sensory components. In all areas of materials science, integrating new abilities into common materials belongs to the most important topics in research and development. In the textile area, several functions can be achieved by finishing techniques, i.e. physical and/or chemical modifications of textile surfaces. The integration of electronic components, however, still suffers from incompatibilities between soft, flexible, bendable textile fabrics and rigid electronic parts. Connecting conductive yarns with electronic components, such as SMD-LEDs etc., cannot be performed by soldering nor by sewing. The typical connection technologies of both areas fail in these cases. A new possibility to achieve such electrical and at the same time mechanical connections is given by 3D printing. In a recent project, we have studied chances and limitations of electric circuits combining textile fabrics with 3D printing. Textile fabrics were woven and knitted from common yarns as well as wires, strands and different conductive yarns. 3D printing was used to connect SMD elements and other small electronic parts with these base circuits and compared with soldered and sewn contacts. The influence of conductive wires, yarns or filaments integrated in the printed elements was tested. The article will give an overview of possibilities and problems in electrical contacting of small electronic components on partly conductive textile fabrics by conductive 3D printed connections. Additionally, an outlook to other potential areas of application, such as sensors and actuators on textile fabrics, is presented.